MODEL OF EXTENDED NOTATION OF ALGORITHM FORMULAS TEXTUAL DESCRIPTION - Ovsiak, O. V. (Radio Electronics, Computer Science, Control, 2011)
The proposed extended xml-notation of algorithm formulas description provides writing of graphical-textual algorithm formulas formed by functional uniterms with ordered variables and parameters in the computer memory. The extended notation model is described by means of algorithm algebra using the sequencing operation. The example of Euclid algorithm formula description using the extended notation is given in the paper.